A Critical Review on Materials and Fabrications of Thermally Stable Separators for Lithium‐Ion Batteries. Issue 5 (16th December 2021) - Wang, Fenfen; Ke, Xinyou; Shen, Kang; Zhu, Lei; Yuan, Chris
Abstract: Li‐ion batteries nowadays are widely used as energy storage systems owing to their high power and energy densities. However, the safety of Li‐ion batteries has increasingly become a grave concern, and how to effectively mitigate or avoid the thermal runaway of Li‐ion batteries, particularly during fast charging/discharging, is a critical issue. It has been pointed out that among various factors governing the safety of Li‐ion batteries, the thermal stability of separators plays an important role. In this review, a critical discussion is reported on recent research and development of thermally stable separators, including surface modified polyolefin separators, novel polymer separators, inorganic structured separators, and functional smart separators, for improving the safety of Li‐ion batteries, summarizing different techniques, processes, and materials being researched and developed for these separators for lithium‐ion batteries. Finally, suggestions are provided on future directions to develop thermally stable separators with respect to the safety of next‐generation Li‐ion batteries. Abstract : This paper provides a critical review of thermally stable separators, including surface modified polyolefin separators, novel polymer separators, inorganic structured separators, and functional smart separators, for improving the safety of Li‐ion batteries, by summarizing different techniques, processes, and materials being researched and developed for these separators. Finally, future directions to develop thermally stable separators with respect to the safety of next generation Li‐ion batteries are suggested.